Cadmium removal from aqueous solution by low-cost native and surface modified Sorghum x drummondii (Sudangrass). Issue 2 (April 2018) - Saraeian, Alireza; Hadi, Atefe; Raji, Foad; Ghassemi, Abbas; Johnson, Michael
Highlights: Equilibrium, kinetics, and thermodynamics of Cd(II) sorption using low-cost Sudangrass was studied for the first time. Various modifying chemicals, i.e. acids, bases, and oxidizers, were used to improve sorption capacity and equilibrium time. Modification using 0.05 M NaOH gave the best results due to the creation of carboxylate sites via ester saponification. Regeneration of the modified sorbent was successfully done for one cycle using 0.5 M HNO3 . Abstract: In an attempt to find inexpensive and effective biosorbents and modification methods, cadmium sorption ability of native Sorghum x drummondii, commonly called sudangrass, and its modified biomass was studied for the first time. From several modified biosorbents, 0.05 M NaOH-modified sudangrass performed the best and hence was used for further experiments. Both sorbents were characterized and various parameters were investigated on their sorption performance. Equilibrium time was reduced from 90 to 20 min after modification. Intra-particle diffusion and pseudo-second order kinetic models were found as best-fitting models for sudangrass and NaOH-modified sudangrass, respectively. Langmuir isotherm model described equilibrium data with the highest accuracy. Maximum monolayer adsorption capacity of cadmium onto sudangrass and NaOH-modified sudangrass was obtained as 1.52 and 7.76 mg g −1, respectively, showing a five-fold improvement for cadmium sorption. Sorption mechanism and thermodynamic investigations suggested that cadmium removal by modified sudangrass is a chemisorption and endothermic process, while cadmium removal by sudangrass is predominantly physisorption and exothermic. This study indicated that both native and modified sudangrass sorbents are capable of removing cadmium ions from aqueous solution with modified biosorbent having a much higher potential for this application.